Respons Hematologi dan Kimia Darah Domba Lokal Indonesia Terhadap Stres Transportasi Selama 12 Jam (HAEMATOLOGICAL AND BLOOD BIOCHEMICAL RESPONSES TO 12 HOUR TRANSPORTATION STRESS IN IN LOCAL INDONESIAN SHEEP) - Sarmin, Sarmin; Hana, Amelia; Astuti, Pudji; Febrianto, Yuda Heru; Airin, Claude Mona (Jurnal Veteriner, 2019)
The objective of this study was to investigate the effect of transport 12 hours on  haematological and some biochemical responses of local Indonesian sheeps.  Ten adults (2.0-2.5 years)  male local Indonesian sheeps  BW adult 30-40 kg were transported by L-300 pickup truck starting at 3:00 pm to 3:00 am on the d 2 without stopping. Jugular blood were collecte-d at 7 am (-8 h pre- transportation as baseline), 15:00  immadiately after (0 h),  19:00 (4 h), 23:00 (8 h) ,  03.00 (12 h ), and at 11.00 d 2 (+8 h)  post-  transportation as recovery period). Under  the conditions of the present study, transport of local Indonesian sheeps significantly increased glucose  during 4 h  transport (P <0.05), increased eosinophil at 0 h (P <0.05) and no significant changed in erythrocytes, haemoglobin , monocytes, neutrophils, lymphocytes, leukocytes,  packed cell volume (PCV), and total plasma protein (TPP) (P> 0.05). Our findings showed that transportation 12 h affected  eosinophil during 0 h and glucose metabolism during 4 h of transportation, but did not any affect on some haematology and dehydration responses in local Indonesian sheeps.